Mircea Eliade e a maturidade do conceito de arquétipo em Carl Jung - Silva, João Victor Sant’Anna (2021)
The main objective of the research was to verify how the maturity of Jung's concept of archetype was influenced by his relationships with Eliade. Therefore, it was verified how the concept of archetype was developed in Jung in a general way, considering his biography and his complete works. Next, the Circle of Eranos was studied, since there Jung found several interlocutors who greatly contributed to the development of his thought. Then he went deeper into the relationship between Jung and Eliade, researching materials that are difficult to access in Portuguese, such as Eliade's diaries and the letters exchanged between Eliade and Jung. It was concluded that Eliade's influence on the maturity of Jung's concept of archetype was mainly due to the work of Eliade “Shamanism” and that this work influenced the turn from the concept of psychoid archetype to archetype as part of the concept of Unus Mundus formulated by Jung. This influence occurred because Jung found in Eliade solid foundations of knowledge that are inaccessible to the psychologist through his personal experience. This allowed Jung a basis to develop his reasoning regarding the universality of archetypal themes, with special focus on the following aspects: the anima archetype, the tree symbolism, quaternity and dismemberment. Still, contact with Eliade's work allowed him to find an important parallel for the symbolism of alchemy in the symbolism of shamanism. It is noteworthy that the friendship between Jung and Eliade, possible hierophanies that occurred in Jung from the reading of the book Eliade's Shamanism, together with other factors, led Jung to elaborate a type of archaic ontology, in which archetypes have a prominent role as part of the notion of Unus Mundus.(AU)